PERSPECTIVE OF MEDIATION EFFECTIVENESS THEORY AS MAIN OPTIONS IN ORDER TO LOWER DIVORCE RATE - Masrur Ridwan; Aryani Witasari; Ahmad Hadi Prayitno (UNISSULA, 2021)
The purpose of this paper is to examine mediation as a way effective to reduce the divorce rate and the obstacles and challenges that create mediation as the means chosen to reduce the divorce rate in Indonesia. The increase and decrease in claimable divorce rates can basically be monitored , if supported by various parties, including through the implementation of effective mediation and efficient. In general, the biggest cause of divorce in Indonesia is dispute continuous and economic problems. Socialization and counseling about coaching the sakinah family has been awarded by the authorities. There is an obligation to conduct mediation before entering the court's domain as regulated in Supreme Court Regulation No.1 of 2016 is still being carried out half-heartedly tends to be mere formality. This is one of the obstacles in the difficulty there is an agreement in the mediation process. The divorce rate can be reduced significantly significant, if the parties involved in household cases have been pushed to take advantage of mediation institutions from an early age. The five elements according to effectiveness theory related to mediation as the main choice in suppressing the divorce rate well done.